STRATEGI APRESIASI DALAM PEMAJUAN KEBUDAYAAN BIDANG SENI DALAM DUNIA PENDIDIKAN - Yudi Nurman Fauzi (Paraguna, 2022)
This paper presents the process of cultural inculturation through an empiricism approach. This cultural inculturation is carried out in the context of efforts to promote culture in the field of art through education. in practice, efforts to promote culture in the arts in the world of education are carried out using art appreciation methods and workshops. This effort is considered to have a fairly high effectiveness in inculturation efforts, because in practice, students who are the targets of inculturation can experience firsthand traditional arts (especially) which are the targets of cultural advancement.